Bridging Clinical Competence and Spirituality through the Integration of an Islamic Curriculum in Medical Professional Education: Literature Review - Ryzka Puput Yunisyar; Andy Visi Kartika; Zulfitriani Murfat (Newinera Publisher, 2026)
The integration of Islamic values into medical professional education has emerged as a critical issue in response to the growing demand for physicians who are not only clinically competent but also possess strong moral and spiritual integrity in medical practice. This study aims to analyze and synthesize scholarly findings on the forms, models, and characteristics of Islamic curriculum integration and its contribution to the development of clinical and spiritual competencies among medical professional students. Employing a literature review method with a narrative integrative review design, this study examines national and international scientific publications published between 2020 and 2025. Data were collected through systematic searches of academic databases, including Google Scholar, PubMed, Scopus, DOAJ, and Garuda (Kemdikbud), and analyzed using narrative synthesis. The findings indicate that the integration of Islamic values within medical professional curricula is implemented through diverse models, ranging from the infusion of Islamic principles into courses and clinical learning, the development of integrated learning modules, to comprehensive institution-wide curricular approaches. Such integration is not reported to hinder the acquisition of clinical skills; rather, it strengthens medical professionalism by reinforcing clinical ethics, professional conduct (adab), empathetic communication, and spiritual awareness in doctor–patient interactions. The Clinical Skills Laboratory emerges as a particularly strategic learning environment for contextualizing and internalizing Islamic values through authentic clinical practice. Nevertheless, the literature also identifies challenges, including limitations in objective and standardized evaluation methods, as well as variability in faculty readiness and institutional capacity. Overall, the integration of an Islamic curriculum holds strong potential as a pedagogical framework for bridging clinical and spiritual competencies in medical professional education, provided it is designed systematically, contextually, and supported by appropriate instructional and assessment strategies.